Environmental Conservation and Social Inequality in Buffer Areas: A Comparative Case Study Analysis - Ilhami, M. Ridha; Subiyakto, Bambang; Rochgiyanti, Rochgiyanti; Abbas, Ersis Warmansyah; Mutiani, Mutiani; Rezeki, Amalia (Universitas Islam Sultan Agung Semarang, 2025)
This study explores how social disparities manifest in environmental conservation efforts within buffer zones of protected areas, adopting a comparative case study approach across ten diverse settings in Asia, Sub-Saharan Africa, Latin America. Drawing on qualitative data, it investigates the distribution of benefits, community engagement, and accessibility to natural resources. The analysis reveals that conservation models driven by incentives frequently deepen pre-existing inequities, particularly when policies are crafted without inclusive consultation or sensitivity to local realities. Common challenges identified include elite capture, resource privatization, limited representation of vulnerable groups, and displacements that disregard customary rights. Despite the presence of community-driven initiatives such as local monitoring schemes and ecotourism ventures their impact is often constrained by inadequate governance structures and superficial community involvement. The research underscores the necessity of embedding principles of justice and equity into conservation frameworks to achieve outcomes that are not only ecologically sound but also socially just. Conceptually, this work contributes to critical debates at the intersection of environmental governance and social equity. Practically, it offers guidance for policymakers to design more context-responsive, participatory, and rights-based conservation strategies. In sum, the findings affirm that sustainable conservation is unattainable without meaningful inclusion and respect for historical and cultural claims.